The Social and Professional Image of the Nurse: Results of an Online Snowball Sampling Survey among the General Population in the Post-Pandemic Period - Ivan Rubbi; Roberto Lupo; Alessia Lezzi; Valeria Cremonini; Maicol Carvello; Martina Caricato; Luana Conte; Marcello Antonazzo; Cosimo Caldararo; Stefano Botti; Vincenzo Andretta; Pio Lattarulo; et al. (MDPI AG, 2023)
Background. The COVID-19 pandemic has transformed people's lifestyles by imposing social, economic, and labor changes. Health professionals have been in the spotlight, occasionally even elevated to the status of "heroes", as they have been at the forefront of the health emergency. Media exposure has undoubtedly played a pivotal role in the evolution and perception of the public's image of nurses, especially within the Italian context. Currently, there is only one study conducted in Italy during the pandemic period. For this reason, we have opted to delve further into this subject during the post-pandemic period, with the ultimate goal of identifying this perceptual evolution. Methods. An online snowball sampling survey was conducted among the Italian population using social networks between August 2022 and January 2023. The survey utilized the Nursing Attitude Questionnaire (NAQ) to collect data. Results. The sample consisted of 564 individuals. Among the respondents, 63.8% (n = 360) were familiar with the nursing pathway, and the level of agreement regarding the training of nurses was 81.5% (n = 260). In terms of recognizing the professional role of nurses, variations emerged in certain domains of the NAQ. Specifically, professional values of nurses were more pronounced in northern and central Italy (M = 26.27). Moreover, stereotypes were more prevalent in the north (23.73 ± 3.538) and the center (23.13 ± 4.104) (p = 0.001). Conclusions. The sample acknowledged a unique competence inherent to nurses that cannot be replaced by other professionals. The study population perceives the nursing profession as pivotal within the IHS (Integrated Health System). However, the attractiveness of the profession remains exceedingly low. This study was not registered on a publicly available registry.